2014
DOI: 10.12968/jowc.2014.23.8.394
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to the treatment of diabetic foot abscesses — a case series

Abstract: Amputation and the removal of infected bone had once been considered the sole treatment for diabetic foot osteomyelitis. Multiple case series and accumulation of clinical experience has shown otherwise, and nowadays medical management of osteomyelitis is the preferred treatment in select patients. In our study, we present a case series of patients suffering from diabetic foot abscesses treated non-surgically. Hopefully this series will lay the foundation for further data demonstrating the feasibility of a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…34,35 Protease-lowering dressings have demonstrated efficacy at removing slough, promoting granulation tissue formation, and stimulating wound repair. CHOOSING THE CORRECT WOUND DRESSING 37 An example of a protease-lowering dressing is the phosphorylated cotton wound dressings prepared to target sequestration of proteases from chronic wound exudate through a cationic uptake binding mechanism involving salt bridge formation of the positively charged amino acid side chains of proteases with the phosphate counter-ions of the wound dressing fiber. 36 Enzymatic debridement is achieved by using proteolytic enzyme preparations, such as collagenase, to digest slough.…”
Section: Fibrinous Wound Beds (Slough)mentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 Protease-lowering dressings have demonstrated efficacy at removing slough, promoting granulation tissue formation, and stimulating wound repair. CHOOSING THE CORRECT WOUND DRESSING 37 An example of a protease-lowering dressing is the phosphorylated cotton wound dressings prepared to target sequestration of proteases from chronic wound exudate through a cationic uptake binding mechanism involving salt bridge formation of the positively charged amino acid side chains of proteases with the phosphate counter-ions of the wound dressing fiber. 36 Enzymatic debridement is achieved by using proteolytic enzyme preparations, such as collagenase, to digest slough.…”
Section: Fibrinous Wound Beds (Slough)mentioning
confidence: 99%
“…PMDs have been shown to be effective in the healing of deep wounds as they are able to perform these roles. 13,37 Other dressings that have traditionally been used to treat deep dermal wounds include alginates, hydrofibers, and hydrogels. 3,6,8 Infected or colonized wounds Dressings should aim to decrease the microbial burden without causing cytotoxic effects.…”
Section: Deep or Tunneling Woundsmentioning
confidence: 99%
“…Furthermore, PMDs are supposed to enhance autolytic debridement, thus promoting a wound cleansing while handling exudates without further trauma . For this purpose, PMDs can also be used for drainage and wound care of abscesses and deep narrow wounds with good results, even in patients suffering from diabetic foot abscesses and osteomyelitis …”
Section: Discussionmentioning
confidence: 99%
“…A prospective crossover study 7 and case series 8,10,12 have shown PMDs continuously cleanse wounds. Overviews, literature reviews, and case series 18,19,32,34,35 support that PMDs release a nontoxic surfactant cleanser 41 to break the chemical bounds between the wound bed and adhering slough, dirt, or other substances that may impair healing. As shown in case series and reviews, 15,19,32,35,36,38 the hydrophilic (water-loving) components of PMDs (the substrate and glycerol, a bacteriostatic simple sugar) pull nutrient-filled, enzyme-rich fluid from the body into the wound bed, enhancing both healing and autolytic debridement.…”
Section: Featurementioning
confidence: 99%
“…Overviews, literature reviews, and case series 18,19,32,34,35 support that PMDs release a nontoxic surfactant cleanser 41 to break the chemical bounds between the wound bed and adhering slough, dirt, or other substances that may impair healing. As shown in case series and reviews, 15,19,32,35,36,38 the hydrophilic (water-loving) components of PMDs (the substrate and glycerol, a bacteriostatic simple sugar) pull nutrient-filled, enzyme-rich fluid from the body into the wound bed, enhancing both healing and autolytic debridement. A case series, 8 a literature review, 35 and a randomized, controlled trial (RCT) 13 found the loosened undesirable substances are drawn into the superabsorbent and substrate of the PMD along with excess fluid.…”
Section: Featurementioning
confidence: 99%